DETEKSI DINI DAN EDUKASI PENYAKIT ASAM URAT DI LINGKUNGAN KELURAHAN KAMBU - Fery Indradewi Armadany; Mesi Leorita; Rifa'atul Mahmudah; Nur Illyyin Akib; Aisyah Said; Dewa Gede Sandhi Yoga; Dwi Sinta; Fina Mei Sridewi; Intan Permatasari Ali Syadikin; Kadek Riani; Ketut Nesa Sawitri; Nur Alifa Muliatan Ramadhani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The increasing prevalence of gout in Indonesia, particularly among the elderly, emphasizes the importance of community-based education and early detection. This community service activity aimed to improve the knowledge of residents of Kambu Village regarding gout, including its risk factors, clinical symptoms, and preventive measures. The program was conducted by the Pharmacy Profession Study Program of Halu Oleo University in collaboration with the UHO Educational Pharmacy and Mokoau Community Health Center during November–December 2025. The methods applied included pre-test, health education sessions, leaflet distribution, interactive discussions, post-test, and free examinations of blood pressure and uric acid levels. A total of 43 participants were involved. The results indicated a significant improvement in participants’ knowledge, as reflected by an increase in correct response rates from 59% in the pre-test to 98% in the post-test. This activity is expected to contribute to gout prevention and improvement of community health outcomes.